Proyecto de factibilidad para la adquisición del club ceibos norte por parte de los copropietaríos al banco de Guayaquil - Mirabá Quirola, Denisse Jazmina (2009)
The present project have the objective to evaluate the economic convenience of the exposition of purchase of Ceibos Norte Club and later administration of its facilities, the same one that has been executed trough the Bank of Guayaquil. During the year 2008, the Bank of Guayaquil proposes the sale of the club 3.362 m2, to the co-owners of the Neighborhood of Ceibos Norte whose commercial estimate is of $420.000 to a maximum term of 15 years. The Administration of the Association of Ceibos Norte “Asoceinort” will evaluate this proposal with the purpose of being owners and managing the remodeling and retraining of its facilities, through a market study that allows to identify variables of decision as far as the preferences of the residents of the Club and its perception of the service that this one offers. In addition It is vital for the attainment of the project to analyze the different alternatives of financing that will allow the potential purchase of the Club.